2021
DOI: 10.21470/1678-9741-2020-0063
|View full text |Cite
|
Sign up to set email alerts
|

Single-Dose Del Nido Cardioplegia vs. Blood Cardioplegia in Aortic Valve Replacement Surgery

Abstract: Introduction In this study, we aimed to compare Del Nido cardioplegia (DNC) with blood cardioplegia (BC) in aortic valve replacement. Methods A two-year single-institute retrospective cohort study was accomplished. Subjects who underwent aortic valve replacement surgery were divided into two groups (DNC and BC) and outcomes were compared. Results Preoperative demographics and clinical data of the patients in both groups were similar. The time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The findings of our study are in line with previously conducted study which states that cardiopulmonary bypass time was statistically significantly shorter in the del Nido group and Del Nido cardioplegia is safe and can be used efficiently in isolated valve replacement surgery. [17][18][19] Our study findings are also supported by recently published systematic review and meta-analysis on del Nido versus blood cardioplegia in adult cardiac surgery. 20 A previous study reported that decreased administration for patients receiving the Del Nido cardioplegia 16 which was inconsistent with this study as we found there was no significant statistical association between the type of cardioplegia and the possibility of receiving the RBCs transfusion.…”
Section: Discussionsupporting
confidence: 87%
“…The findings of our study are in line with previously conducted study which states that cardiopulmonary bypass time was statistically significantly shorter in the del Nido group and Del Nido cardioplegia is safe and can be used efficiently in isolated valve replacement surgery. [17][18][19] Our study findings are also supported by recently published systematic review and meta-analysis on del Nido versus blood cardioplegia in adult cardiac surgery. 20 A previous study reported that decreased administration for patients receiving the Del Nido cardioplegia 16 which was inconsistent with this study as we found there was no significant statistical association between the type of cardioplegia and the possibility of receiving the RBCs transfusion.…”
Section: Discussionsupporting
confidence: 87%
“…Based on preliminary analysis against patient-specific cases, we identify four governing parameters, namely EF , E / A , , , able to embed key information on LV geometry and function. We provide a probabilistic description for the governing parameters by using uniform distributions, with ranges of variation covering both healthy and diseased conditions 15 , 35 41 (see Table 1 ). A parameterized geometry, based on the combination of two patient-specific cases and varying only as a function of the governing parameters, is used for the purpose of generating the surrogate models.…”
Section: Resultsmentioning
confidence: 99%
“…27) Furthermore, the combined delivery of magnesium with lidocaine may provide further protection on ischemic cardiomyocytes by inhibiting the influx of intracellular protons to increase intracellular glycogen utilization and thus to provide more ATP stores during ischemia arrest period. 8,18) The reported positive effects of DNC on arrhythmias included lower incidence of VF during cross-clamping period, 11,21,23,25) lower postoperative AF, 21) higher ratio spontaneous restoration of sinus rhythm, 10,12) and less post ACC release defibrillation requirement. 25) The detailed mechanism for these benefits is not completely clear.…”
Section: Discussionmentioning
confidence: 99%